Peran Big Money dalam Pasar Modal Indonesia: Analisis Dampak terhadap Likuiditas, Harga Saham, dan Arah Sentimen Pasar - Muhammad Fahmi; Gumulya Sonny Marcel Kusuma; Muhammad Faris Afif; Junyka Widiyanti (Universitas Muhammadiyah Palembang, 2025)
The main objective of this study is to analyze the role of Big Money in the Indonesian capital market. Specifically, the objectives of this study are to analyze the characteristics and behavior of Big Money in the Indonesian capital market, examine the impact of Big Money on Indonesian capital market liquidity, and identify the influence of Big Money on stock price movements in the Indonesian capital market. Secondary data from 2001-2024 was used. Data collection techniques were web scraping, observation, documentation, and literature review. The study found that Big Money plays a significant role in increasing liquidity through high trading volumes, but also triggers sharp fluctuations and volatility in stock prices, risking negatively impacting retail investors. Furthermore, big data-based fintech applications enable more accurate market predictions, creating an imbalance in access to information between large and small investors. This study emphasizes the importance of strict regulations to control the impact of Big Money in order to maintain market balance and protect all parties involved.